Magnetic control without attitude determination for spinning spacecraft. (April 2020) - Cubas, Javier; de Ruiter, Anton
Abstract: In this article, a magnetic control without attitude determination for spinning spacecraft is presented. The control only uses magnetorquers as actuators and sun-sensors and magnetometers as sensors. An equilibrium angular velocity is reached by using two magnetic moments at the same time; the first one is a B-dot control that produces a despinning torque based in magnetic measurements; the second one produces a spinning torque using an inertial reference, such as the sun's direction as viewed from the spacecraft. The final orientation of the spin is normal to the orbit, parallel to sun direction or an intermediate angle between them. This orientation is controlled by setting different dissipation gains or using gravitational gradient. Control performance has been analyzed mathematically and demonstrated with Monte Carlo tests for Sun-synchronous orbits. A methodology to estimate adequate control gains is also presented. Highlights: New magnetic control that uses inertial reference for spinning spacecraft is proposed. Attitude determination is not required. Control performance is proven for noon-midnight sun-synchronous orbit.